Computation of Constant Gain and NF Circles for 60 GHz Ultra-low noise Amplifiers - Gnanamani, Christina; Pandiaraj, Shanthini (IRO Journal on Sustainable Wireless Systems, 2021)
Wireless communication is a constantly evolving and forging domain. The action of the RF input module is critical in the radio frequency signal communication link. This paper discusses the design of a RF high frequency transistor amplifier for unlicensed 60 GHz applications. The Transistor used for analysis is a FET amplifier, operated at 60GHz with 10 mA at 6.0 V. The simulation of the amplifier is made with the Open Source Scilab 6.0.1 console software. The MESFET is biased such that Sll = 0.9
Keywords: Millimetre wave; amplifier; FET; gain; transistor; Scilab